Intercontinental hotels group: time to check-in? - valuation in times of a global pandemic - Michel, Paulina (2021)
2020 has been a disrupting year, especially for the tourism industry due to the Covid-19 pandemic with a significant travel drop. We see IHG's revenue at pre-Covid levels in 2024. Due to the successful vaccine development's during the past two months, we are confident that the group's occupancy rates, and average daily rates will start to recover in the second half of 2021. However, IHG will need to face a decreased level of business travel for the next years. We see a total return for shareholders of 7.42% within one year, due to IHG's expansion in Greater China, flexible working solutions, the asset-light business model and the continuous urge to improve to compete with peer-to-peer accommodations. After conducting a DCF analysis and a comparable company analysis, we consider a share price of £49.82 (31/12/2021) as target share price.